Komparasi Politik Privatisasi Air Inggris Dan Indonesia - Eva Nur Laily Rohmah (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Provision of public services is a government reponsibility that must be carried out for the community. Privatization is one of the various models of management of public services that exist in the government. The definition of privatization is the transfer of part of the government’s authority to the private sector in providing services to the community, with the aim of increasing efficiency and reducing the burden on APBN. This article was written to compare the practices of privatization of water resources in England and Indonesia through literature studies. Privatization is one of the model of governance cariied out by the government in a state to realize efficiency and excellent service. England and Indonesia apply the privatization model in providing water sector services. Providing public services in practicing for the government to realize the welfare of its people. Especially in the water sector, because water is a vital resource that is the main need of the people. At the conclusion of this article, in practice the application of the privatization of the England and Indonesian Water sectors did not run well. Therefore, there have been several attempts to respond this issue. One of them is regulating efforts. Even in Indonesia the Water Resources Law was canceled, therefore private ownership of water resources management is limited